Heat transfer performance of closed conduit turbulent flow: Constant mean velocity and temperature do matter! - Zubir, Mohd Nashrul Mohd; Muhamad, M.R.; Amiri, A.; Badarudin, Ahmad; Kazi, Salim Newaz; Oon, C.S.; Abdullah, H.T.; Gharehkhani, S.; Yarmand, Hooman (Elsevier, 2016)
Present paper focused on the study of the role of thermophysical properties of nanofluid in changing convective heat transfer and hydrodynamic performances in the conduit flow. The investigation was conducted in a 2-D pipe flow model assigned with specific boundaries while a set of constitutive equations based on finite volume approach were established to solve the model. A fully developed boundary profile for velocity and turbulent parameters was adopted at the inlet which serves as the new approach for investigation of nanofluid to obtain more accurate and faster convergence results. TiO2 nanoparticle dispersed in water was used in the present study. The plots of the wall parameters showed that the fully developed benchmark was attained at axial distance, x < 1D in comparison to the conventional approach of using constant inlet boundary profiles which require x > 5D. Plots of thermophysical property profiles showed extreme variation from the near wall to the turbulent core regions. It was found that, at mean velocity ratio of unity between the base fluid and nanofluid, the heat transfer augmentation manifested at low velocity and particle concentration. The results highlighted negative heat transfer enhancement above 3% v particle concentration, indicating the degradation of heat transfer performance with increasing particle loading.